2022
DOI: 10.1016/j.gpb.2022.06.002
|View full text |Cite
|
Sign up to set email alerts
|

GREPore-Seq: A Robust Workflow to Detect Changes After Gene Editing Through Long-Range PCR and Nanopore Sequencing

Abstract: To achieve the enormous potential of gene-editing technology in clinical therapies, one needs to evaluate both the on-target efficiency and unintended editing consequences comprehensively. However, there is a lack of a pipelined, large-scale, and economical workflow for detecting genome editing outcomes, in particular insertion or deletion of a large fragment. Here, we describe an approach for efficient and accurate detection of multiple genetic changes after CRISPR/Cas9 editing by pooled nanopore sequencing o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Cannot distinguish between deletions and CN-LOH (Alanis-Lobato et al 2021 ; Leibowitz et al 2021 ; Przewrocka et al 2020 ; Simkin et al 2022 ; Weisheit et al 2020 ; Zuccaro et al 2020 ) Targeted short- and long-amplicon sequencing Targeted PCR amplification followed by NGS Can detect SVs housed completely within the amplicon Limited to SVs housed completely within the amplicon. Allele quantification is prone to PCR and sequencing bias (Kosicki et al 2018 ; Quan et al 2022 ; Simkin et al 2022 ; Wen et al 2021 ; Yoo et al 2022 ) Individual DNA molecule sequencing (IDMseq) Individual DNA molecules are labeled with UMIs followed by the generation of short- or long amplicons and NGS Detect and quantify SVs housed completely within the amplicon Limited to SVs housed completely within the amplicon (Bi et al 2020 ) Linear amplification-mediated high-throughput genome-wide translocation sequencing (LAM-HTGTS) Linear amplification across a target DSB site using a biotinylated primer. Amplicons are enriched by streptavidin selection and are further amplified after the ligation of an adapter.…”
Section: Methods To Detect Structural Variants In Crispr-edited Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannot distinguish between deletions and CN-LOH (Alanis-Lobato et al 2021 ; Leibowitz et al 2021 ; Przewrocka et al 2020 ; Simkin et al 2022 ; Weisheit et al 2020 ; Zuccaro et al 2020 ) Targeted short- and long-amplicon sequencing Targeted PCR amplification followed by NGS Can detect SVs housed completely within the amplicon Limited to SVs housed completely within the amplicon. Allele quantification is prone to PCR and sequencing bias (Kosicki et al 2018 ; Quan et al 2022 ; Simkin et al 2022 ; Wen et al 2021 ; Yoo et al 2022 ) Individual DNA molecule sequencing (IDMseq) Individual DNA molecules are labeled with UMIs followed by the generation of short- or long amplicons and NGS Detect and quantify SVs housed completely within the amplicon Limited to SVs housed completely within the amplicon (Bi et al 2020 ) Linear amplification-mediated high-throughput genome-wide translocation sequencing (LAM-HTGTS) Linear amplification across a target DSB site using a biotinylated primer. Amplicons are enriched by streptavidin selection and are further amplified after the ligation of an adapter.…”
Section: Methods To Detect Structural Variants In Crispr-edited Cellsmentioning
confidence: 99%
“…NHEJ-inhibitors (e.g., M3814 or NU7441), which inhibit key NHEJ repair pathway proteins, such as KU or DNA-PK4, have been shown to improve HDR-efficacy by four- to five-fold, independent of the target loci (Chu et al 2015 ; Riesenberg et al 2019 ). However, recently it has been shown that inhibition of NHEJ proteins results in increased incidence of large deletions, insertions, translations and chromosomal truncations as a result of CRISPR-Cas-mediated DNA cleavage (Do et al 2012 ; Kosicki et al 2022 ; Liu et al 2021 ; Quan et al 2022 ; Wen et al 2021 ). Therefore, broad detection of editing outcomes, including on-target SVs, is essential for primary research and clinical therapies which incorporate the use of NHEJ-inhibitors.…”
Section: Evidence For Crispr-associated Svsmentioning
confidence: 99%
“…1C; Supplementary Table S3). We computed the metric of deletion indexes and D100 (deletion of over 100bp) using our published pipeline GREPore-seq (30). Surprisingly, deletion indexes in the edited liver samples were indistinguishable from wildtype controls, with only 0.3% observed.…”
Section: Low Levels Of Large Deletions After In Vivo Crispr Editing I...mentioning
confidence: 99%
“…Proportions of deletion were de ned as (read depth − mean depth) / (read depth) and obtained using the command "Samtools coverage le.bam." of Samtools (30,48). As detailed in the earlier research, we also categorized the removal of fragments exceeding 100bp (D100) as large deletions (12,49).…”
Section: Large Deletion Analysis -Deletion Indexesmentioning
confidence: 99%
See 1 more Smart Citation